Factors affecting the implementation of governance policy in land administration in Kenya A case study of Nairobi county - Kathiga, Nancy Njeri (My University, 2012)
The importance that the people of Kenya attach to land is enormous. Up to the early eighties, investors and business people acquired land based on the need to develop and establish a business. Rarely would one purchase land for speculation. Currently, people have been claiming ownership to land that was originally planned for roads, schools, hospitals and other public utility uses. Buildings worth millions of shillings have been demolished to pave way for road construction as they were built on land planned for road construction. All these are a result of poor governance of land administration. This study sought to find out the factors that affect the implementation of governance policy of land administration in Kenya. The specific objectives were to determine the effect of the land administration structure, politics and the records keeping systems in the implementation ofgovernance policy of land administration. fhe research study targeted the land administrators who are in charge of land administration in the country while on the other hand targeting the landowners in the area of study. Using questionnaires and interview schedule, the researcher sought to derive findings and recommend measures to be used in the implementation of governance policy in land administration. Amongst the key findings obtained by the researcher, the record keeping system came out as the main impediment to the implementation of governance policy of land administration. Primarily, the record keeping system in the Ministry of Lands was found to be the manual keeping system although automation was ongoing. In this regard, the researcher recommended that automation should be expedited. Another finding of the research concerned the operation of the registry and its operations. In addition, members of the public complained about the bureaucracy at the ministry as an impediment to implementation of governance policy of land administration. Amongst the recommendations, the key one was the implementation of the constitution article on devolution. In this regard, the devolved system of government would reduce some of the bureaucratic processes in land administration. As such, taking land administration services to the grassroots would enhance implementation of governance policy in land administration. Furthermore, the new constitution's articles on governance and land administration should be implemented fully. Another key recommendation is on the fast-tracking of automation land records. finally, future researchers should research on the challenges posed by emerging issues, such as rapid urbanization and population pressure, to implementation of governance policy in land administration. It is evident that the officials in the Ministry of Lands are not adequately equipped to deal with matters resulting from rapid urbanization and population pressures. Thus, the extent they played towards good governance should be clearly investigated.